Positive Psychological Functioning Scale in Spanish Adolescents (PPF-A) - Merino, Mª Dolores; Privado, Jesús (Anales de Psicología / Annals of Psychology, 2024)
We are presenting the adaptation and validation of a Positive Psychological Functioning scale in Spanish adolescents in a sample of 1,858 (M = 14.50 years, SD = 2.87 years), previously developed for adults (Merino & Privado, 2015b). The adaptation presents a hierarchical structure of one general factor and 11 of first order that suitably explain the data (GFI = 0.966, NFI = 0.966, SRMR = 0.053). The reliability (internal consistency and test-retest) is adequate. Evidence of convergent and discriminant validity of the test was found with other measures of subjective well-being, psychological well-being, positive and negative affect, and personality. The test has predictive validity on clinical symptoms (R2 = 0.17) and there are no differences in the measure based on sex and the period of adolescence considered (early, middle and late). Finally, scales for the sample evaluated are provided.